TEACHERS' EXPERIENCES IN INTEGRATING LOCAL WISDOM INTO PHYSICAL EDUCATION TEACHING: A PHENOMENOLOGICAL STUDY AT SMPN SEKECAMATAN BANGKINANG, KAMPAR REGENCY - Sri Agustina Ratnawati; Ria Rafianti (Indonesia Sport Journal, 2025)
This study aims to describe the experiences of physical education teachers in junior high schools in Bangkinang Subdistrict in implementing basic movement learning based on local wisdom, the assessment process, and the challenges faced. This qualitative study involved PJOK teachers as informants through interviews and observations. The results showed that teachers attempted to integrate elements of Riau Malay culture into basic movement activities, but implementation was not optimal due to limitations in guidance, facilities, and conceptual understanding. In the final assessment, teachers still used a general assessment format, which did not fully reflect local cultural values. The study recommends the development of a learning model and guidelines based on local wisdom so that implementation and assessment are more focused.